Implementation of Curriculum Management Based on Ke'aisyiyahan Values - Aslamiah, Aslamiah; Noorhapizah, Noorhapizah; Azzahra, Humaira Salwa (Journal of English Language and Education, 2025)
Early Childhood Education (ECE) plays a crucial role in shaping children's character and moral foundation. One of the key aspects that supports this is religious education, which, through a curriculum based on Islamic values, instills noble character from an early age. This study aims to examine the implementation of curriculum management based on the Ke'Aisyiyahan values at TK Aisyiyah Bustanul Athfal 32 Banjarmasin. Using a descriptive qualitative approach, this research explores the planning, implementation, and evaluation of the curriculum that integrates the Merdeka Curriculum with Islamic values. The findings indicate that curriculum planning is carried out through internal workshops that align the Merdeka Curriculum with the Ke'Aisyiyahan Guidelines. The learning process is conducted using thematic methods and projects that instill religious values, such as love for plants and daily prayers. Evaluation is performed regularly through weekly observations, which are then discussed in monthly evaluation meetings to adjust teaching strategies. This study provides insights into the implementation of a values-based curriculum in ECE, focusing on the development of Islamic character and emotional intelligence from an early age. This curriculum is expected to shape students who are not only intellectually capable but also possess strong character and high spirituality.